«Intellekt-xarita» - fizika va astronomiya bo‘yicha talabalar faoliyatini rivojlantirish va faollashtirish vositasi sifatida - Karlibaeva, G.E.; Embergenova, K. (SCIENCE and SOCIETY, 2021)
The article discusses one of the graphical methods of presenting information, namely the technique of "mind map", proposed the principles and rules for constructing the structure of mind-map, features and advantages of using this method in the educational process.
Keywords: mind-map; structure of mind map; students; physics; astronomy